PENGARUH BADAN USAHA MILIK DESA ( BUMDES) “KEMBAR SARI “ TERHADAP PENINGKATAN PEREKONOMIAN MELALUI POTENSI DESA BANYUASIN KEMBARAN (STIE Rajawali Purworejo, 2024)
Village-Owned Enterprises, hereinafter referred to as BUMDes, are an alternative to improving the regional economy in rural areas, and are usually managed by local residents, for education and training, BUMDes are of course tailored to the needs, so from the start you must know what needs are needed to realize success of BUMDes, training or education for villages that are about to establish BUMDes or do not have sufficient resources to establish BUMDes, so the education and training needed are basic accountants and how to establish BUMDes and the position of BUMDES has not been completely regulated in statutory regulations. existing or PERDEs (Village Regulations) on the basis of a Village Head Decree. The purpose of this study was to analyze the use of village funds in Banyuasin Kembaran Village in accordance with the PDIT Permendesa and to analyze what factors hinder the process of using village funds in Banyuasin Kembaran Village for BUMDes development.The form of research used is descriptive , with data collection techniques through interviews with informants who are considered to have the potential to provide information about BUMDes in Banyuasin Kembaran Village. The results of this problem show that the human resources of the village apparatus are different, the development of the economic base in rural areas has long been carried out by the government through various programs. However, these efforts have not yielded the satisfactory results that we all wanted. Many factors contributed to the unsuccessfulness of these programs. One of the most dominant factors is too large a government intervention, as a result it inhibits the creativity and innovation of rural communities in managing and running economic machines in rural areas.